2018
DOI: 10.1021/acsami.8b01588
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Structural and Electrical Properties of Carbon Films from Amorphous Carbon to Nanocrystalline Graphene on Quartz Glass by HFCVD

Abstract: Direct growth of graphene films on glass is of great importance but has so far met with limited success. The noncatalytic property of glass results in the low decomposition ability of hydrocarbon precursors, especially at reduced temperatures (<1000 °C), and therefore amorphous carbon (a-C) films are more likely to be obtained. Here, we report the hydrogen influence on the structural and electrical properties of carbon films deposited on quartz glass at 850 °C by hot-filament chemical vapor deposition (HFCVD).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 60 publications
3
32
0
Order By: Relevance
“…The carrier density given by equation 3is quoted to around 10 20 -10 21 cm -3 . It must be noted that the transport properties obtained, with mobility of around 20 cm 2 /V.s at the best, are quite comparable with a recent publication on ta-C:H samples annealed at higher temperatures [35].…”
Section: ) Transport Measurementssupporting
confidence: 88%
“…The carrier density given by equation 3is quoted to around 10 20 -10 21 cm -3 . It must be noted that the transport properties obtained, with mobility of around 20 cm 2 /V.s at the best, are quite comparable with a recent publication on ta-C:H samples annealed at higher temperatures [35].…”
Section: ) Transport Measurementssupporting
confidence: 88%
“…So, hydrogen atoms can promote the topological order of the graphite phase and the increase of the aromatic hydrocarbon bond. Besides, the amorphous property and poor thermal conductor of NBR rubber may accumulate sufficient plasma activation energy and lead to random nuclei of graphite phase [34]. The load-displacement curves further demonstrate that DLC films prepared by the increasingly hydrogenated CH 4 gas discharge plasma own relatively inferior mechanical properties (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…, thereby producing small grain size and impairing the mechanical properties of the film [34]. In addition, the previous results demonstrate that hydrogen atoms passivate the dangling bonds generated on the friction interfaces and prevent the adhesive component [22].…”
Section: Resultsmentioning
confidence: 93%
“…The many favorable properties of nanocrystalline carbon films have allowed for a great development in a wide range of applications, such as surface modification, , electric and thermal conductivity modulation, , and energy storage and conversion. In these applications, the grain size and growth orientation of nanocrystals can significantly impact their physical and chemical properties. For instance, researchers have found that by changing the grain size and growth orientation of graphite-like nanocrystals, nanocrystalline carbon films may exhibit very different properties of through-film resistance and atmospheric surface absorption. , However, despite that, many techniques including substrate catalysis, , ion bombardment, , and electron ,, and laser irradiations have been developed to increase the nucleation density of graphene-based nanocrystals, as researchers continue seeking more effective and precise methods to accelerate the nucleation process and to control the grain size and growth orientation of nanocrystalline carbon films.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma-assisted depositions, mainly including plasma enhanced chemical vapor deposition (PECVD) and magnetron sputtering deposition in combination with an unbalanced magnetron configuration, , have become major techniques in the preparation of nanocrystalline carbon films. Since these bottom-up growth processes always involve the Ostwald’s ripening of carbon nuclei, whether the initial carbon nuclei are crystallized can significantly influence the final microstructures of nanocrystalline carbon films.…”
Section: Introductionmentioning
confidence: 99%